2004
DOI: 10.1093/ajcn/80.4.903
|View full text |Cite
|
Sign up to set email alerts
|

Iron and zinc supplementation promote motor development and exploratory behavior among Bangladeshi infants

Abstract: The beneficial effects of weekly iron and zinc supplementation on motor development and orientation-engagement suggest that infants benefit from these minerals when administered together.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
199
1
19

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 226 publications
(226 citation statements)
references
References 25 publications
7
199
1
19
Order By: Relevance
“…Conversely, more recent randomized control trials from India (Taneja et al, 2005) and Bangladesh (Black et al, 2004), where malnutrition is common among children, did not find that zinc supplementation alone affects infants' cognitive development on the Bayley Scales of Infant Development test. Nevertheless, in the Bangladeshi trial, when zinc was combined with iron supplementation, it showed an improvement in cognition (Black et al, 2004). Additional studies are therefore needed to examine the long term benefit of zinc on brain development.…”
Section: Zincmentioning
confidence: 84%
“…Conversely, more recent randomized control trials from India (Taneja et al, 2005) and Bangladesh (Black et al, 2004), where malnutrition is common among children, did not find that zinc supplementation alone affects infants' cognitive development on the Bayley Scales of Infant Development test. Nevertheless, in the Bangladeshi trial, when zinc was combined with iron supplementation, it showed an improvement in cognition (Black et al, 2004). Additional studies are therefore needed to examine the long term benefit of zinc on brain development.…”
Section: Zincmentioning
confidence: 84%
“…Similarly Kemppinen, Kumpulainen, Moilanen and Ebeling (2006) found that 75% of mothers who were identified as being "at risk" in lack of sensitivity towards their infant 6 to 8 weeks postpartum, also reported depressive symptoms. Evidence shows that depressed mothers are less sensitive towards their babies (Murray et al, 1996;Steadman et al, 2007), being more intrusive or withdrawn (Black et al, 2007;Field, Hernandez-Reif & Diego, 2006;Herrera, Reissland & Shephard, 2004;) and less accurate in interpreting their baby's emotions (Broth, Goodman, Hall & Raynor, 2004). Similarly paternal depression has been associated with a less optimal father -infant relationship (Field, Hossain & Malphurs, 1999;Field, 2010; for a review, see Wilson & Durbin, 2010) with examples of less involvement with their child (Roggman, Boyce, Cook & Cook, 2002).…”
Section: Parental Mental Health and Parent-infant Interactionsmentioning
confidence: 99%
“…Zinc deficiency is a serious problem in developing countries. Many studies have shown the adverse effects on growth and morbidity as well as the prevention of infection by zinc supplementation in pregnant women, infants and children (Bates et al, 1993;Goldenberg et al, 1995;Brown et al, 1998;Bhutta et al, 1999;Caulfield et al, 1999;Shankar et al, 2000;Osendarp et al, 2001;Black et al, 2004). Zinc deficiency has also been reported in industrialized countries.…”
Section: Introductionmentioning
confidence: 99%